A Systematic Review Exploring AI’s Role in Self-Regulated Learning Within Education Contexts - Liling Ren; Kerry Lee; Lawrence May (IEEE Access)
The application of Artificial Intelligence (AI) in education has attracted much attention, and self-regulated learning (SRL) is a key competency for student development and an important factor for student academic success in the current digital environment. Therefore, it is crucial to understand the status of AI applications in SRL. To this end, we conducted a systematic review of AI applications in SRL in the educational context by searching the literature from 2004 to 2024, with 27 studies meeting the final inclusion criteria. The results of the final literature analysis revealed trends in the educational level, research method, subject area application of AI on SRL, common types of AI used to support SRL in education, the relationship between AI and the SRL theories used, and the outcomes of the application of AI to SRL. Finally, implications for empirical research on the application of AI in SRL are also discussed.